Gunshot wounds to the liver: No longer a mandatory operation. Issue 2 (August 2019) - Schellenberg, Morgan; Benjamin, Elizabeth; Piccinini, Alice; Inaba, Kenji; Demetriades, Demetrios
Abstract : BACKGROUND: Selective nonoperative management (SNOM) of gunshot wounds (GSWs) to the liver is a contemporary management strategy that remains controversial. This study examined national trends and outcomes after SNOM versus operative management (OM) of hepatic GSWs. METHODS: The National Trauma Data Bank was used to identify patients who sustained an isolated GSW to the liver (2007–2014). Patients with emergency department death, transfer, or associated hollow viscus or major abdominal vascular injury were excluded. The defined study groups were SNOM versus OM, with SNOM specified as patients who did not undergo laparotomy within 4 hours of admission. Outcomes included mortality and complications. Logistic regression was used to compare outcomes between groups. RESULTS: A total of 4, 031 patients were included, with 38.8% (n = 1, 564) undergoing SNOM and 61.2% (n = 2, 467) undergoing OM. The rate of SNOM increased over time, from 34.5% to 41.0% ( p = 0.004). By the American Association for the Surgery of Trauma liver injury grade, SNOM was used in 45.0% of grades I and II, 40.6% of grade III, 27.3% of grade IV, and 16.7% of grade V injuries. On regression analysis, SNOM was independently associated with fewer complications (odds ratio [OR], 0.811; p = 0.003) and lower mortality (OR, 0.438; p < 0.001). On subgroup analysis, patients with grade IV injury were most likely to benefit from SNOM with fewer complications (OR, 0.676; p = 0.019) and improved mortality (OR, 0.238; p = 0.002). CONCLUSION: Selective nonoperative management of GSW to the liver has gained acceptance in the United States. Selective nonoperative management is independently associated with improved survival and decreased complications. In the appropriate clinical scenario, SNOM is a safe and effective method for treating hepatic GSWs. LEVEL OF EVIDENCE: Therapeutic/care management, level III.